Lineage Status and Inheritance Rights of Children from Interfaith Marriages According to the Compilation of Islamic Law (KHI) - Afrianto, Afrianto (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Marriage, lineage, and inheritance law are three interrelated things in human life, because marriage is one of the causes of obtaining lineage and inheritance. From the marriage, lineage can be created and mutual inheritance between husband and wife as well as children and parents. However, it is different if an interfaith marriage occurs, because religious differences are one of the factors that hinder lineage and inheritance. The purpose of this study is to determine and analyze: 1) The legal status of interfaith marriage according to the Compilation of Islamic Law; 2) The lineage status of children born from interfaith marriages according to the Compilation of Islamic Law; 3) Heirs of children from interfaith marriages according to the Compilation of Islamic Law. The research method in this study uses a statutory approach, thus this study is included in the category of normative legal research. The legal materials used are qualitative, consisting of primary legal materials in the form of laws and court decisions, as well as secondary legal materials in the form of literature, doctrines, and other scientific works. The collection of legal materials was carried out through library research, while the analysis technique used is qualitative descriptive analysis to provide a systematic description of the legal norms being studied. The research results concluded: 1)The legal status of children in interfaith marriages creates legal uncertainty, both according to Indonesian positive law and Islamic law. In the national legal system, the validity of the marriage is the basis for determining whether a child is legitimate or not. Because interfaith marriages are not recognized according to Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage, then legally children born from such marriages cannot be categorized as legitimate children in the context of Islamic law; 2) From the perspective of Islamic law as stipulated in the Compilation of Islamic Law (KHI), children resulting from a marriage between a Muslim man and a non-Muslim woman do not have a lineage relationship with their father. This is based on the principle that interfaith marriages are invalid in Islam, so they do not give rise to civil legal consequences in the form of determining lineage. Thus, the child's lineage can only be traced to the mother, as regulated in Article 100 of the KHI which emphasizes that illegitimate children only have a lineage relationship with their mother and their mother's family; 3) The implications for inheritance rights cannot be ignored. Because there is no blood relationship between a child and their father in an interfaith marriage, there is no inheritance relationship between them. This is in line with Article 171 letter c and Article 186 of the Compilation of Islamic Law, which states that inheritance only occurs between Muslims and those related by blood or by a valid marriage. Therefore, children of an interfaith marriage are not entitled to inherit from their Muslim father, and vice versa, except through a grant or mandatory will within certain limits.